2019
DOI: 10.1080/09500693.2019.1571649
|View full text |Cite
|
Sign up to set email alerts
|

Discourse forms in a classroom transitioning to student-centred scientific inquiry through co-teaching

Abstract: Teacher-student discourse continues to be teacher-centred even though researchers and reform documents have recommended changes toward increased levels of student-centred discourse. In science education this situation is paralleled by effort to make scientific inquiry more student-centred. The purpose of this study was to investigate how discourse forms changed over time in a classroom where the regular teacher and his students were scaffolded in the transitioning to student-centred scientific inquiry. Video-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Despite the preliminary nature of the study, the research has nonetheless shown that interest in dialogic teacher talk situations is likely higher than interest in non-dialogic teacher talk situations. It is known that dialogic talk is rare (Lehesvuori et al, 2013), but change towards more dialogic forms of classroom talk is possible (Rees & Roth, 2019). Therefore, this paper provides additional support for teachers to emphasise dialogic teaching because it may develop student interest in science lessons.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the preliminary nature of the study, the research has nonetheless shown that interest in dialogic teacher talk situations is likely higher than interest in non-dialogic teacher talk situations. It is known that dialogic talk is rare (Lehesvuori et al, 2013), but change towards more dialogic forms of classroom talk is possible (Rees & Roth, 2019). Therefore, this paper provides additional support for teachers to emphasise dialogic teaching because it may develop student interest in science lessons.…”
Section: Discussionmentioning
confidence: 98%
“…Although the goal of collective sensemaking has been accepted for quite a while, multiple studies over time continue to show that IRE and other similar closed, teacher-centered discourse forms remain the most common in science classrooms (e.g. Nassaji & Wells, 2000;Pimentel & McNeill, 2013;Rees & Roth, 2019;Scott et al, 2006;Wells & Mejia Arauz, 2006). Nevertheless, researchers have observed and characterized other discussion patterns in science classrooms.…”
Section: Discussion In Science Classroomsmentioning
confidence: 99%
“…This pattern can either be a repeated sequence with one student or a more interactive sequence in which multiple different students respond to the teachers' feedback (Mortimer & Scott, 2003). Similarly, Rees and Roth (2019) characterized the I-R-Q-R-A form of classroom discourse, in which the teacher initiates a conversation (I), a student responds (R), and the teacher and student(s) proceed through rounds of clarifying questions (Q), responses, and non-evaluative acknowledgement of the responses (A). Taken together, these studies show that classroom talk can be much more complex than the well-known IRE structure.…”
Section: Discussion In Science Classroomsmentioning
confidence: 99%
See 2 more Smart Citations